Dyspnea in pulmonology - Kozielski, Jerzy (Przewodnik Lekarza/Guide for GPs Supplement, 2007)
Dyspnea is one of the most common symptoms of pulmonary diseases. The mechanism of origin, methods of dyspnea evaluation as well as the origin both acute and chronic dyspnea are presented in the paper. Differential diagnosis of the symptom, in relation to its origin, is also described in the paper.